2015
DOI: 10.1186/s12913-015-0954-5
|View full text |Cite
|
Sign up to set email alerts
|

Preventing mental illness: closing the evidence-practice gap through workforce and services planning

Abstract: BackgroundMental illness is prevalent across the globe and affects multiple aspects of life. Despite advances in treatment, there is little evidence that prevalence rates of mental illness are falling. While the prevention of cardiovascular disease and cancers are common in the policy dialogue and in service delivery, the prevention of mental illness remains a neglected area. There is accumulating evidence that mental illness is at least partially preventable, with increasing recognition that its antecedents a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
27
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 115 publications
(76 reference statements)
1
27
0
Order By: Relevance
“…With the far higher rate of multiple adversity, we find 22.5% of indigenous children between the ages of 4 and 10 years report high levels of psychological distress (using the SDQ total problems score), compared with just over 8% of children of the same age in LSAC 29. Other studies put rates of psychological distress in Australian children higher, across a broad age range 21, 44, 45, 46…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…With the far higher rate of multiple adversity, we find 22.5% of indigenous children between the ages of 4 and 10 years report high levels of psychological distress (using the SDQ total problems score), compared with just over 8% of children of the same age in LSAC 29. Other studies put rates of psychological distress in Australian children higher, across a broad age range 21, 44, 45, 46…”
Section: Discussionmentioning
confidence: 66%
“…It forms part of a larger research program to apply an evidence‐informed needs‐based planning framework to determine the optimal workforce and service structure required to deliver best practice in preventive mental health care29 (complementing recent work by Guy et al30 on rates of risk exposure in predominantly nonindigenous Australian children).…”
mentioning
confidence: 99%
“…In addition, by school age, children's environments have expanded considerably to include school and peer networks, adding to the complexity of an intervention that should ideally address the child's entire ecosystem (Coie et al, 1993). Thus, early family-based preventative interventions that target at-risk families are often considered to be optimal for preventing future mental health problems (Furber et al, 2015). For example, one analysis found that parenting interventions aimed at preventing conduct problems in the United Kingdom had a 25-year return on investment of at least eight times the initial costs of intervention in the form of decreased public expenses associated with health care, social services, and the justice system (Knapp, McDaid, & Parsonage, 2011).…”
mentioning
confidence: 99%
“…Using the needs-based health workforce planning framework, the healthcare needs of this population can be mapped against best practice care to estimate total health workforce requirements. 44 This model has already been applied to regional populations with diabetes 45 and mental illness, 46 and takes a far more ‘richer perspective on population needs’ than other workforce planning approaches. 44 Given the considerable health workforce maldistribution in regional South Australia, 47–49 this is an important next step for this research.…”
Section: Discussionmentioning
confidence: 99%